MENINGKATKAN KEMAMPUAN BERBICARA PADA ANAK USIA 5-6 TAHUN MELALUI METODE BERMAIN PERAN DI PAUD PELANGI KASIH KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Hutabarat, Renofa; Jas, Jaspar; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This study aimed to investigate the effect on the ability of activities Role Playing Talking Children. The study consists of two variables: Speech and Role Playing The hypothesis proposed in this study are as follows: Through the implementation of role-playing activities can improve speaking skills of children aged 5-6 years in early childhood Pekanbaru Pelangi Kasih